A Methodology for Reading Tafsir Manuscripts: Philological and Hermeneutical Analysis within the Framework of Qirā’ah al-Nuṣūṣ - Ilham Murtala; Andi Abdul Hamzah; Mohammad Harjum (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the methodology of reading tafsir manuscripts (qirā’ah al-nuṣūṣ) through philological and hermeneutical approaches and to explain the urgency of integrating both approaches within contemporary Qur’anic exegesis studies. The study is motivated by the tendency of tafsir scholarship to separate textual validity, which constitutes the primary concern of philology, from contextual interpretation, which is the central focus of hermeneutics. This research employs a qualitative-descriptive library research method. Data were collected from various primary and secondary sources, including books, journal articles, and other scholarly works relevant to the research topic. Data collection was conducted through documentary research, while data analysis employed content analysis of the selected literature. The findings reveal that philology plays a crucial role in ensuring textual authenticity and validity through manuscript criticism, collation, and textual reconstruction, whereas hermeneutics functions to interpret textual meaning based on historical and social contexts as well as the reader’s horizon of understanding. Although these approaches differ in orientation, they are complementary in the interpretative process. This study concludes that the integration of philology and hermeneutics constitutes an ideal methodological framework for reading tafsir manuscripts, as it maintains a balance between textual validity and contextual relevance. Consequently, such an integrated approach produces interpretations that are both academically rigorous and contextually meaningful in addressing the challenges of contemporary tafsir studies.